Macrocyclic peptides that inhibit Wnt signalling via interaction with Wnt3a. Issue 1 (24th March 2020) - Otero-Ramirez, Manuel E.; Matoba, Kyoko; Mihara, Emiko; Passioura, Toby; Takagi, Junichi; Suga, Hiroaki
Abstract : Discovery and optimization of de novo macrocyclic peptide binders of Wnt3a through RaPID screening against an afamin-stabilized Wnt3a complex, capable of inhibiting Wnt signalling by direct interaction to the Wnt protein. Abstract : Here we report de novo macrocyclic peptide binders to Wnt3a, a member of the Wnt protein family. By means of the Random non-standard Peptides Integrated Discovery (RaPID) system, we have performed in vitro selection against the complex of mouse Wnt3a (mWnt3a) with human afamin (hAFM) to discover macrocyclic peptides that bind mWnt3a with K D values as tight as 110 nM. One of these peptides, WAp-D04 (Wnt–AFM-peptide-D04), was able to inhibit the receptor-mediated signaling process, which was demonstrated in a Wnt3a-dependent reporter cell-line. Based on this initial hit, we applied a block-mutagenesis scanning display to identify a mutant inhibitor, WAp-D04-W10P, with 5-fold greater potency in a reporter assay. This work represents the first instance of molecules capable of inhibiting Wnt signaling through direct interaction with a Wnt protein, a molecular class for which targeting has been challenging due its highly hydrophobic nature.